Molecular and morphological assessment of the Liopholis inornata (Rosén, 1905) species group (Reptilia: Squamata: Scincidae), with descriptions of two new species from northern Western Australia - Aplin, Ken P.; Maryan, Brad; Armstrong, Kyle N.; Pavey, Chris R.; Donnellan, Stephen C. (Zootaxa, 2024)
Molecular genetic and morphological assessments were undertaken on the Liopholis inornata species group of skinks that occur on sandy soils in both mesic and arid regions of Australia. The primary objective was the taxonomic identification of two outlying peripheral populations from the North-West Cape and Purnululu National Park, in northern Western Australia. To provide adequate context, molecular genetic and morphometric variation was assessed across the wide geographic range of L. inornata, a taxon that is strongly phylogeographically structured. It was also necessary to reassess the taxonomic identity of two previously named taxa from central Australia, L. s. slateri (Storr) and L. s. virgata (Storr). Phylogenetic analyses of nuclear SNPs from extant populations confirm that L. inornata, L. s. slateri and the two outlying populations from northern Western Australia are each distinct evolutionary lineages. Prior to analyses of the extent of morphological divergence between the lineages, we assessed the extent of morphometric differences between the sexes using two well-sampled species, L. inornata and L. striata (Sternfeld) from Western Australian populations. We determined that while males have relatively longer, wider and deeper heads throughout life these differences are relatively slight and the data from both sexes could be pooled for subsequent morphological interspecific comparisons. The two outlying populations are distinguished from congeners based on phylogenetic relationships and divergence in nuclear nucleotide sequences and distinctive morphometric and colour attributes and thus represent new species. The new species both occur in biogeographically significant areas that contain several other endemic reptile species. Liopholis s. virgata, for which we currently lack genetic data, is morphometrically and chromatically different from all the other taxa and very likely represents a distinct species that is potentially extinct as it has not been sighted for more than a century.